Determinants of idea sharing in crowdsourcing: evidence from the automotive industry - Thomas Schäper; J. Nils Foege; Stephan Nüesch; Sebastian Schäfer (R&D Management, 2021)
Drawing on external ideas through crowdsourcing has become common practice for firms that seek to improve and extend their product portfolios. As these initiatives often address the users of products, it is essential for firms to recognize those attributes that determine these individuals' willingness to share their ideas. This study takes the example of the automotive industry to examine how three attributes of car drivers determine their sharing behavior – that is, altruism, psychological ownership of ideas, and trust in car manufacturers. Our findings suggest that trust and altruism strengthen idea sharing, while psychological ownership weakens it. Furthermore, we find that car drivers' perception of sharing-related risk acts as an important boundary condition for these relationships.
Keywords: 650